2020
DOI: 10.1111/bld.12339
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and plan of care at end of life: Perspectives of people with intellectual disabilities and families in Ireland

Abstract: Accessible summary Professionals are reluctant to discuss sensitive information with people with intellectual disabilities. People with intellectual disabilities and families wish to engage in end‐of‐life discussions. People with intellectual disabilities expressed how they could handle bad news and they felt that this information could be used to help make choices. People with intellectual disabilities and families want to develop a plan based on their choices and wishes and there is a need to respect this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The findings of this study are in line with other Ireland-based research on end of life care for this population. It supports the suggestion, made in other Irish studies on this topic, that that the family is an important determining factor in if and to what extent this population's end of life wishes are heard and respected (Cithambaram et al, 2020;McCausland et al, 2019). Our study brings in an additional focus on home-based versus institution-based end of life care, an aspect which, to our knowledge, has not been examined in an Irish context before.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study are in line with other Ireland-based research on end of life care for this population. It supports the suggestion, made in other Irish studies on this topic, that that the family is an important determining factor in if and to what extent this population's end of life wishes are heard and respected (Cithambaram et al, 2020;McCausland et al, 2019). Our study brings in an additional focus on home-based versus institution-based end of life care, an aspect which, to our knowledge, has not been examined in an Irish context before.…”
Section: Discussionsupporting
confidence: 89%
“…The 25 included articles represent 23 studies. Five included papers (20%) (Cithambaram et al, 2019, 2020; Tuffrey‐Wijne et al, 2009; Tuffrey‐Wijne, Bernal, & Hollins, 2010; Tuffrey‐Wijne, Bernal, Hubert, et al, 2010) reported on two studies. One methodological paper (Butler et al, 2012) reviewed two articles, with one article included in the review (Tuffrey‐Wijne et al, 2012) and one was not (Tuffrey‐Wijne, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen of the included studies (68%) reported levels of intellectual disabilities (see Table 1). Nine studies (53%) (Cithambaram et al, 2019, 2020; Cithambarm et al, 2021; Forrester‐Jones, 2013; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; Thorp et al, 2018; Tuffrey‐Wijne et al, 2013) collected data from people with mild to moderate disabilities and all used interviews. Five studies (29%) (Chow et al, 2017; Rodríguez Herrero et al, 2015; Tuffrey‐Wijne et al, 2009; Tuffrey‐Wijne, Bernal, & Hollins, 2010; Tuffrey‐Wijne, Bernal, Hubert, et al, 2010) collected data from people with mild, moderate, and severe intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…. .the person who is dying should know everything and people should let them make choices [First order data 92 ] A key concern for primary participants was that they were able to make their own choices and be in control of the decisions being made. [Second order data 93 ] ‘The discussions about wishes also seemed to express a deep desire that the person with ID should be in control’.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…. .the person who is dying should know everything and people should let them make choices [First order data 92 ]…”
Section: Uncertaintiesmentioning
confidence: 99%